2019
DOI: 10.1590/0103-8478cr20180791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herbage allowances on biomass flows in Italian ryegrass

Abstract: The objective of this study was to determine the leaf tissue flows in Italian ryegrass (Lolium multiflorum Lam.), in different phenological stages, grazed by lambs, and managed under three herbage allowances (6, 9 and 12 kg DM/100 kg body weight under rotational stocking method. The experimental design was completely randomized, with repeated measures arrangement. Forage allowances determined similar growth and intake flows, actual and potential utilization efficiencies of grass and they were different in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…BARGO et al (2003) suggested that appropriate values for animals fed solely with pastures range from 3 up to 5 times more than that estimated for dry matter intake, and 2.5 times higher when animals receive supplements. Furthermore, FA values from experiments analyzed in the present study were within the range indicated by GRAMINHO et al (2019), from 6 to 12 kg of DM per 100 kg of BW for ryegrass management, without jeopardizing foliar tissue fluxes and efficiency of pasture use. The sum of the average supplement intake and forage allowance totaled 10 kg of DM per 100 kg of BW, similar to the forage allowance of heifers maintained only on pastures.…”
Section: Resultssupporting
confidence: 70%
“…BARGO et al (2003) suggested that appropriate values for animals fed solely with pastures range from 3 up to 5 times more than that estimated for dry matter intake, and 2.5 times higher when animals receive supplements. Furthermore, FA values from experiments analyzed in the present study were within the range indicated by GRAMINHO et al (2019), from 6 to 12 kg of DM per 100 kg of BW for ryegrass management, without jeopardizing foliar tissue fluxes and efficiency of pasture use. The sum of the average supplement intake and forage allowance totaled 10 kg of DM per 100 kg of BW, similar to the forage allowance of heifers maintained only on pastures.…”
Section: Resultssupporting
confidence: 70%
“…In southern Brazil, annual ryegrass (Lolium multiflorum Lam.) has great importance in livestock systems, in which the ryegrass is a spring-winter growth, in which is stands out for having high nutritional species value and can be used in the efficient and economically viable production of lambs, which are animals with high nutritional requirements (GRAMINHO et al, 2019). This is due to a number of characteristics of this grass including high forage yield, good quality, good nutritional value, adaptation to different types of soil, and natural reseeding capacity (CONTERATO et al, 2016;FONTOURA et al, 2020).…”
Section: Introductionmentioning
confidence: 99%